Ecologizar a memória: sertão, antropologia e crise ecológica no século XXI - Pereira, Renan Martins (2023)
Memory and ecology are the subjects that form the fundamental ethnographic relationship of this thesis. My central argument is that Anthropology has distanced memory from its ecological and environmental issues. Faced with this theoretical finding, the challenge of this work is to try to reverse this supposed scenario of ecological ineffectiveness of memory in four different ways. In Chapter I, the actions of memory are guided and rhythmed by the desolation of the world and by the planetary ecological crisis of the 21st century. In Chapter II, I intend to give vigor to the forces of creation of a memory directed against oblivion and social isolation produced by the Covid-19 pandemic. In Chapter III, I intend to analyze the memory in Floresta, a municipality in the hinterland of Pernambuco, seeking to understand particularly how the historical memory of conflicts unfolds in this location in a historical memory of traditions. As an exclusively traditional form of memory, the old sertão cowboys and their experiences from ancient times make up the arguments of the fourth and final chapter. In Chapter IV, I elaborate an analysis of how the memories of the drought unfold temporally in a memory of plenty of the old cattle ranches. Facing the contemporary scenario of successive deaths of the environment (burning forests, mineral waste, toxic mud, epidemics, pandemics, droughts and desertification), I defend the hypothesis according to which the act of remembering is not a mere regression to the past. The past is itself a present element in the processes of creation, composition and improvement of reality. Henri Bergson's philosophy thus gains a privileged place in this thesis for offering to ethnography a conception of memory that cannot be reduced to the social forces of reproduction and representation. Above all, remembering is an ecological and vital act. It’s a way of keeping alive the relationships with the world.